The traveller's prayers: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story highlights the special supplications and practices for those on a journey, emphasizing the importance of prayer in seeking guidance and protection. It teaches children about the significance of connecting with Allah during travel and the comfort that faith provides in new experiences and challenges.